Γεωμετρικός σχεδιασμός αυτοκινητόδρομου - Κανελλοπούλου, Ευμορφία (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
The writing of this thesis aims at understanding the basic principles of a Highway Geometric Design. First of all, key concepts are analyzed and explained so they will set the foundation for the next level, the level of Road Development. Specifically, the study of the different kinds of Road Groups, which are established by the Research Road Works Directives (OMOE), the Speed limits that are used in Design, as well as the Slope Across the Road Axis and Cross Slope is been written. Thereafter, an explanation of the utility of Contour Curves and study how the Isoklinis Line making process, as well as the final performance of Polygon Line, are explained. The Horizontal Alignment is followed and more specifically the analysis of the Horizontal Curve and the characteristics of the Spiral Curve. At the end of the chapter a Kilometer Process is been given. The Design of the Longitudinal Section is followed and before that a procedure of calculations for the Altitude of the Center Line is done. Meanwhile, a brief reference to performance of Zero Line is been written. After that, the Design and the calculation of the Borderline Street, as well as the Cross Sections in Cutting, Backfill and a Combination of the above are being made. The elements Visibility and of course the application of Visibility for Attitude, both in plain view, and in the Vertical Alignment are included in the thesis. In conclusion, for the understanding all of the above, a procedure is carried out for the Geometric Design of a Road Project, in which each phase is resolved, obeying the applicable boundaries and criteria Planning.
Keywords: Geometric Design; Category of road; Along slope; Cross slope; Contour curve; Isoklinis line; Polygon line; Horizontal alignment; Spiral curve; Longitudinal section; Center line; Zero line; Cross section; Visibility; Γεωμετρικός σχεδιασμός; Κατηγορία οδού; ΟΜΟΕ; Κατά μήκος κλίση; Επίκλιση; Ισοϋψής καμπύλη; Ισοκλινής γραμμή; Πολυγωνική γραμμή; Οριζοντιογραφία; Κλωθοειδής καμπύλη; Μηκοτομή; Ερυθρά; Μηδενική γραμμή; Διατομή; Ορατότητα